2012
DOI: 10.1371/journal.pone.0031187
|View full text |Cite
|
Sign up to set email alerts
|

Tri-Axial Dynamic Acceleration as a Proxy for Animal Energy Expenditure; Should We Be Summing Values or Calculating the Vector?

Abstract: Dynamic body acceleration (DBA) has been used as a proxy for energy expenditure in logger-equipped animals, with researchers summing the acceleration (overall dynamic body acceleration - ODBA) from the three orthogonal axes of devices. The vector of the dynamic body acceleration (VeDBA) may be a better proxy so this study compared ODBA and VeDBA as proxies for rate of oxygen consumption using humans and 6 other species. Twenty-one humans on a treadmill ran at different speeds while equipped with two loggers, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
291
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(297 citation statements)
references
References 51 publications
6
291
0
Order By: Relevance
“…Because of the strong relationship between total ODBA and total VeDBA (R 2 =0.99, t 15 =211.4, P<0.0001), we only considered a single total DBA formulation for AIC analysis. Total ODBA was omitted given its marginally poorer performance and because of the theoretical arguments put forward by Gleiss et al (2011) and Qasem et al (2012). The most parsimonious model identified by AIC analysis for predicting DLW-estimated mass-specific total energy expenditure was a total VeDBA model parameterizing surface swimming separate from all other modes of locomotion (Table 1) Table S1), but time budget models were also highly sensitive to activity parameterization in comparison to the relatively robust total VeDBA models.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the strong relationship between total ODBA and total VeDBA (R 2 =0.99, t 15 =211.4, P<0.0001), we only considered a single total DBA formulation for AIC analysis. Total ODBA was omitted given its marginally poorer performance and because of the theoretical arguments put forward by Gleiss et al (2011) and Qasem et al (2012). The most parsimonious model identified by AIC analysis for predicting DLW-estimated mass-specific total energy expenditure was a total VeDBA model parameterizing surface swimming separate from all other modes of locomotion (Table 1) Table S1), but time budget models were also highly sensitive to activity parameterization in comparison to the relatively robust total VeDBA models.…”
Section: Resultsmentioning
confidence: 99%
“…However, Gleiss et al (2011) raised concerns about ODBA, arguing non-independence in the axes of motion and advocating instead for the use of vectorial dynamic body acceleration (VeDBA). In comparing these two interpretations of DBA, Qasem et al (2012) found little difference between the VeDBA and ODBA. However, this study was selfacknowledged as being limited in scope, given its investigation into only a single activity (treadmill walking) in humans and a small number of captive animal species.…”
Section: Introductionmentioning
confidence: 84%
“…VeDBA is a vectorial measure of the total dynamic movement of the animal and has been used as a proxy for energy expenditure [47]. Any movement due to changes in speed by the animal or as a result of turbulence that the animal experiences from the environment will manifest itself in the VeDBA.…”
Section: Patterns In Body Posture and Motionmentioning
confidence: 99%
“…The 2 methods (line interpolation and SD) were computed for each axis of these data se quen ces. For each sequence, dynamic acceleration values were summed across the 3 axes, yielding overall dynamic body acceleration (ODBA; Wilson et al 2006, Qasem et al 2012. In this way, we were able to directly compare the 2 methods used to compute ODBA.…”
Section: Validation Of Simple Algorithms To Measure Dynamic and Statimentioning
confidence: 99%
“…The most common measure of dynamic acceleration is ODBA, which includes accelerations from all 3 axes in its computation (Qasem et al 2012). However, one could reduce the number of axes measured as a proxy for ODBA (see Gleiss et al 2010).…”
Section: Data Reduction: Dynamic Accelerationmentioning
confidence: 99%